Type the correct answer in the box. Use numerals instead of words.

Use the order of operations to evaluate this expression:

7 + (5 – 9)2 + 3(16 ÷ 8).


The value of the expression is
.

1 answer

To evaluate the expression \(7 + (5 - 9)^2 + 3(16 \div 8)\), follow the order of operations:

  1. Evaluate the expression inside the parentheses: \[ 5 - 9 = -4 \]

  2. Square the result: \[ (-4)^2 = 16 \]

  3. Evaluate \(16 \div 8\): \[ 16 \div 8 = 2 \]

  4. Multiply by 3: \[ 3 \times 2 = 6 \]

  5. Now substitute back into the original expression: \[ 7 + 16 + 6 \]

  6. Finally, perform the addition: \[ 7 + 16 = 23 \] \[ 23 + 6 = 29 \]

The value of the expression is 29.